Courts, litigants, and the digital age: law, ethics, and practice - Eltis, Karen (Irwin Law, 2016)
Courts, Litigants, and the Digital Age examines the ramifications of technology for courts, judges, and the administration of justice. It sets out the issues raised by technology, and, particularly, the Internet, so that conventional paradigms can be updated in the judicial context. In particular, the book dwells on issues such as proper judicial use of Internet sources, judicial ethics and social networking, electronic court records and anonymization techniques, control of the courtroom and jurors' use of new technologies, asnwell as the Internet's impact on judicial appointments and the diversity of thenjudiciary. The second edition includes discussion of current issues in thisnrapidly developing area, such as privacy protection, the "right to be forgotten," cyber intimidation, freedom of digital speech, and litigant anonymity. Through examination of relevant practical, legal, and ethical issues, it endeavours to extract lessons from the developing issues surveyed and proposes forward-thinking approaches based on proportionality principles.